INCREASING DUST-CHAMBER EFFICIENCY OF ROTARY FURNACE FOR MAGNESITE TREATMENT - Spisak, Jan; Nascak, Dusan; Oravcova, Eva (European Scientific Journal, ESJ, 2015)
Magnesite is a basic carbonate material used as caustic magnesia in agriculture and industry and as raw material for the production of sintered magnesia. As a basic refractory material, the magnesite is mainly used for high-temperature aggregates in the mining and processing industry. In the mechanical and heat treatment of magnesite due to decrepitation of magnesite, a number of fine grained and dust particles are formed. Currently, only part of the material is processed. This paper presents new opportunities for improving the capture process of dust wastes (flue dust). The solution is focused on application to the rotary kilns (RP). The proposed solution allows a significant contribution to the capture and subsequent treatment of the flue dust. Thus, partially implemented adjustments create the possibility of effective recovery of this type of waste.